Motion Events in The Holy Qur’an: “Surah Yusuf” a Model A Cognitive Semantic Approach - fakhry Elieba (Beni-Suef University International Journal of Humanities and Social Sciences, 2020)
AbstractCognitive Semantics is a sub-field from linguistics. It is relatively a modern linguistic approach that emerged during the 1970s. The term Cognition represents the process of people's thoughts, beliefs, attitudes and perceptions. This approach is closely related to philosophy, psychology, and other cognitive sciences. Some scholars including Lakoff (1987), Langaker (1987a) Talmy (1985, 1991, 2000a/b) and Fauconnier (1997) are among the leading figures in this field. This study discusses and scrutinizes the relationship between language and the human mind, in addition, the way words are created in mind. This study is intended to study cognitive linguistics aspects including Motion Events in the Holy Quran (Surah Yusuf) from a cognitive semantic perspective. This perspective can cast more light on the significance of cognitive abilities of image schemas, Figure and ground relationship together with Motion and Path Events. The results show that Motion Events have an important role in providing the semantic structure of this type of verbs can help to reveal some fascinating aspects of meaning construction in the Holy Qur’an. This study also reveals that the semantic network around these verbs goes beyond the process of delivering to perceptual and conceptual delivery. Accordingly, verbs of motion essentially transmit information about manner of movement in which path is delineated.